2015
DOI: 10.1097/md.0000000000001913
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Myxoma Leading to Stroke

Abstract: Primary cardiac tumors are rare, and most are myxomas. Only approximately 5% of cardiac myxomas originate from the ventricles.We report the case of a 23-year-old man presenting with right hemiplegia and muscle strength degeneration under a diagnosis of stroke. Transthoracic echocardiography revealed a 29 × 26 mm mass arising from the anterior interventricular septum. The tumor was surgically removed, and histology confirmed the diagnosis of left ventricular myxoma.We report its clinical features and treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Compared with LV thrombosis, the typical LV myxoma has higher mobility and narrower base. Kong Y et al [ 4 ] reported a TTE finding of LV myxoma leading to stroke. Through TTE, Qin W et al [ 12 ] observed a LV myxoma attached at the base of the anterolateral papillary muscle in a patient with no history of syncope, palpitation, or dyspnea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with LV thrombosis, the typical LV myxoma has higher mobility and narrower base. Kong Y et al [ 4 ] reported a TTE finding of LV myxoma leading to stroke. Through TTE, Qin W et al [ 12 ] observed a LV myxoma attached at the base of the anterolateral papillary muscle in a patient with no history of syncope, palpitation, or dyspnea.…”
Section: Discussionmentioning
confidence: 99%
“…However, Left ventricular (LV) myxoma could be located in any part of the left ventricle. [ 4 ] LV myxoma is usually benign, but may lead to fatal consequences including emboli and cardiac arrhythmias resulting in sudden death. [ 5 , 6 ] Because of the deadly outcome of this disease, it is important to make a correct diagnosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation